2007
DOI: 10.1242/jeb.02775
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific comparison of hydrodynamic performance and structural properties among intertidal macroalgae

Abstract: Macroalgae use flexibility and reconfiguration, i.e. the alteration of shape, size and orientation as water velocity increases, to reduce the hydrodynamic forces imposed in the wave-swept rocky intertidal zone. Quantifying the effects of flexibility on hydrodynamic performance is difficult, however, because the mechanisms of reconfiguration vary with water velocity and the relationship between algal solid mechanics and hydrodynamic performance is poorly understood. In this study, the hydrodynamic performance, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 33 publications
1
41
0
Order By: Relevance
“…Comparisons with the flexibility of macroalgae is difficult since flexibility measures typically used in macroalgae studies are different from flexural rigidity (e.g. the ratio E t /E c of 'Tension' E t and 'Compression' Young's moduli E c as in Biedka et al 1987;Gaylord and Denny 1997; structural flexibility as in Boller and Carrington 2007; or 'Tension' Young's modulus E t as in Denny and Gaylord 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Comparisons with the flexibility of macroalgae is difficult since flexibility measures typically used in macroalgae studies are different from flexural rigidity (e.g. the ratio E t /E c of 'Tension' E t and 'Compression' Young's moduli E c as in Biedka et al 1987;Gaylord and Denny 1997; structural flexibility as in Boller and Carrington 2007; or 'Tension' Young's modulus E t as in Denny and Gaylord 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Most aquatic vegetation is flexible and becomes streamlined with increasing flow velocities and it is very difficult to measure accurately the frontal area under waves and currents (SandJensen 2003(SandJensen , 2005; but see Boller and Carrington 2007). For this reason, the total surface area was used as the frontal area as it can be accurately measured.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that macroalgae exhibit a highly adaptable flow structures to reduce their resistance to flow [3,4,19]. The connection between the algae size and drag coefficient is not straightforward and depends on the thallus branches, flexibility, compressibility and physiological ability of a specific species to adapt to flows.…”
Section: The Impact Of Macroalgae Hydrodynamic Properties On the Offsmentioning
confidence: 99%
“…The connection between the algae size and drag coefficient is not straightforward and depends on the thallus branches, flexibility, compressibility and physiological ability of a specific species to adapt to flows. These relationships between hydrodynamic and structural properties depend on velocity of the water [3,4,19]. In Fig.…”
Section: The Impact Of Macroalgae Hydrodynamic Properties On the Offsmentioning
confidence: 99%